APPLICATION OF COMMON DATA ENVIRONMENT (CDE) AS A METHOD OF DESIGN REVIEW IN CONSTRUCTION PROJECT - Sabrina Ayu Lestari; Hari Purwanto; Jonathan Saputra (Logic : Jurnal Rancang Bangun dan Teknologi, 2022)
Abstract. The development of technology in construction projects produces a method known as Building Information Modelling (BIM). Common Data Environment (CDE) is one of the cloud technology adoption systems that can effectively convey various data information from several BIM softwares without having to download the softwares. Searching for accurate project information according to the latest version takes a long time if the document or information is not well structured. This study aims to analyze the application of CDE to the project in the design review and to determine the criteria that affect the success of the implementation of CDE in the design review and the biggest obstacles in the use of CDE. This research was conducted using a survey method which was distributed to representative respondents. The results showed that the implementation of CDE as a design review on the project was in accordance with CDE standards with an average respondent's level of achievement of 83.28%. The most influential criterion on the success of CDE implementation in the design review is data security. The biggest obstacles are in the form of lack of cooperation between CDE users, undisciplined use, and data that is not always updated.